Effect of surfactants and polyethylene glycol on the activity and stability of a lipase from oilseeds of Pachira aquatica - Polizelli, Patricia Peres [UNESP]; Tiera, Marcio Jose [UNESP]; Bonilla-Rodriguez, Gustavo Orlando [UNESP] (Springer, 2008)
Lipases from oilseeds have a great potential for commercial exploration as industrial enzymes. Lipases are used mixed with surfactants in cleaning and other formulated products, and accordingly, both components must be compatible with each other. This work presents the results of the effects of anionic, cationic and nonionic surfactants, polyethylene glycol and urea on the activity and stability of a lipase extracted of oilseeds from Pachira aquatica. The enzyme was purified and the spectrophotometric assays were done using p-nitrophenyl acetate (p-NPA) as substrate pH 7.5 and 25 degrees C. The activity was significantly enhanced by the cationic surfactant CTAB. Bile salts increased the lipase activity in the tested concentration range, whereas anionic and nonionic surfactants showed an inhibitory effect. Aqueous solutions of PEG activated the lipase and maximum activation (161%) occurred in PEG 12,000. This effect on lipase that can be due to exposition of some hydrophobic residues located in the vicinity of the active site or aggregation.
Keywords: oilseeds; Lipase; Surfactant; Polyethylene glycol; bile salts; urea